Gastroesophageal Reflux Disease – Health-Related Quality of Life Questionnaire: prospective development and validation in Italian. Issue 3 (9th September 2020) - Balla, Andrea; Leone, Giuseppe; Ribichini, Emanuela; Sacchi, Maria Carlotta; Genco, Alfredo; Pronio, Annamaria; Paganini, Alessandro M.; Badiali, Danilo
Abstract : Objective: To date, two questionnaires investigating the symptoms of gastroesophageal reflux disease (GERD) (Quality of Life Reflux and Dyspepsia and Reflux Disease Questionnaire) are validated in Italian, but neither of the two questionnaires was correlated with an instrumental examination. The aim of the present study is to improve the GERD-Health Related Quality of Life (HRQL) questionnaire, to evaluate the reliability and validity of its Italian translation, and its sensitivity and specificity. Methods: A modified Italian GERD-HRQL (MI-GERD-HRQL) questionnaire was developed adding six questions investigating on regurgitation, for a total of 15 questions. The forward-backward translation process was employed to obtain a definitive from-English-to-Italian version. Data obtained from the questionnaire were compared to upper gastrointestinal endoscopy findings. Results: The questionnaire was administered twice to 130 Italian-speaking patients by two different and independent raters. Cronbach's α of the first and second questionnaire was 0.944 and 0.942, respectively. Spearman correlation and inter-rater reliability were 0.923 and 0.929, respectively. Sensitivity and specificity were 73.3 and 64%, and 69.5 and 64%, respectively, for the first and second questionnaire. Conclusion: The MI-GERD-HRQL questionnaire proved good consistency, reliability, sensitivity and specificity in the evaluation of typical GERD symptoms.